2019
DOI: 10.1177/2309499019831454
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryotherapy on quadriceps electromyographic activity and isometric strength in patient in the early phases following knee surgery

Abstract: To determine the effects of cryotherapy on quadriceps electromyographic (EMG) activity and isometric strength in early postoperative knee surgery patients. Methods: Twenty-two volunteers with recent knee surgeries were included. EMG readings of the vastus medialis (VM), rectus femoris (RF), and vastus lateralis (VL) from the surgical leg were collected during a maximal voluntary quadriceps setting (QS) activity. Maximum isometric knee extension force measurements were also recorded. Subjects were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
(60 reference statements)
0
23
1
Order By: Relevance
“…The purpose of the current study was to determine static (isometric) and dynamic (isokinetic) quadriceps strength following FKJC. If we found the expected improvements during isometric contraction that were consistently documented in the literature [20][21][22], the improvement would translate to isokinetic (dynamic) strength because of ice-induced mechanical changes [26] and/or neuromuscular facilitations [25,28]. We hypothesized that FKJC would significantly improve both isometric and isokinetic quadriceps strength as measured by peak torque output.…”
Section: Introductionmentioning
confidence: 84%
“…The purpose of the current study was to determine static (isometric) and dynamic (isokinetic) quadriceps strength following FKJC. If we found the expected improvements during isometric contraction that were consistently documented in the literature [20][21][22], the improvement would translate to isokinetic (dynamic) strength because of ice-induced mechanical changes [26] and/or neuromuscular facilitations [25,28]. We hypothesized that FKJC would significantly improve both isometric and isokinetic quadriceps strength as measured by peak torque output.…”
Section: Introductionmentioning
confidence: 84%
“…Literature data demonstrated the stimulus effect of low temperature on the bioelectrical activity of the muscle as assessed by sEMG. It was for example demonstrated that change in skin temperature changed the EMG signal without any change in muscle activity in healthy volunteers (Winkel & Jørgensen, 1991) (Holewijn & Heus, 1992) The influence of low temperature on sEMG signal was assessed for different forms of exposure: cold climate chamber (temperature 14 • C) (Winkel & Jørgensen, 1991), local and whole body cooling (15 • C water) (Holewijn & Heus, 1992) (Solianik et al, 2015) (Piedrahita et al, 2009), ice bag (Loro et al, 2019) (Akehi et al, 2016), localized air-pulsed cryotherapy (-30 • C), (Gilhem et al, 2013), and WBC (Westerlund et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that cooling superficial tissues roughly doubles the sEMG amplitude, for example in healthy volunteers (Winkel & Jørgensen, 1991), and patients with symptoms of spasticity (Harlaar et al, 2001) as well as in patients in the early phases following knee surgery (Loro et al, 2019). It is known that tempera- Asmussen et al, 1976).…”
mentioning
confidence: 98%
See 2 more Smart Citations